2008
DOI: 10.1152/ajplung.00278.2007
|View full text |Cite
|
Sign up to set email alerts
|

20-HETE increases superoxide production and activates NAPDH oxidase in pulmonary artery endothelial cells

Abstract: oxygen species (ROS) signal vital physiological processes including cell growth, angiogenesis, contraction, and relaxation of vascular smooth muscle. Because cytochrome P-450 family 4 (CYP4)/20-hydroxyeicosatetraenoic acid (20-HETE) has been reported to enhance angiogenesis, pulmonary vascular tone, and endothelial nitric oxide synthase function, we explored the potential of this system to stimulate bovine pulmonary artery endothelial cell (BPAEC) ROS production. Our data are the first to demonstrate that 20-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 45 publications
(60 reference statements)
7
90
0
Order By: Relevance
“…It has also been shown to exert proinflammatory actions. In vascular endothelial cells, 20-HETE increases ROS, including superoxide (3,8,16), and stimulates NF-B activity (4,13), resulting in endothelial activation with increased expression of ICAM-1 and IL-8 levels (13). 20-HETE-dependent increases in NADPH oxidase, ROS, and NF-B activity are also seen in the renal microvasculature of androgen-treated rats (28,39).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to exert proinflammatory actions. In vascular endothelial cells, 20-HETE increases ROS, including superoxide (3,8,16), and stimulates NF-B activity (4,13), resulting in endothelial activation with increased expression of ICAM-1 and IL-8 levels (13). 20-HETE-dependent increases in NADPH oxidase, ROS, and NF-B activity are also seen in the renal microvasculature of androgen-treated rats (28,39).…”
Section: Discussionmentioning
confidence: 99%
“…Fresh bovine PAECs were isolated as previously described ( 11 ). The pulmonary tissues were obtained from a local slaughterhouse with all protocols reviewed and approved by the Ethical Committee of Laboratory Animals at Harbin Medical University.…”
Section: Cell Culturementioning
confidence: 99%
“…It has been reported that 20-HETE acts as a potent vasoconstrictor of cerebral microvessels (Harder et al, 1994), and has an important role in the autoregulation of cerebral blood flow (Gebremedhin et al, 2000). 20-Hydroxyeicosatetraenoic acid has also been reported to induce the formation of oxygen radicals by interacting with nicotinamide adenine dinucleotide phosphate-oxidase and nitric oxide synthase (Wang et al, 2006;Cheng et al, 2008;Medhora et al, 2008). Previously, we reported that brain and plasma 20-HETE levels were significantly increased in the rat transient middle cerebral artery occlusion (tMCAO) model (Tanaka et al, 2007), and inhibition of 20-HETE synthesis by N-(3-chloro-4-morpholin-4-yl)phenyl-N'-hydroxyimido formamide (TS-011), a selective inhibitor of CYP4s, improved the autoregulatory dysfunction in the peri-infarct microcirculation and the neurologic outcomes in rat and monkey stroke models by reducing the infarct volume of the brain after ischemia (Miyata et al, 2005;Omura et al, 2006;Tanaka et al, 2007;Marumo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%